Effect of the conditional cash transfer program on the incidence of pulmonary tuberculosis in Dominican Republic (2012-2018) - Duarte Duarte, Francisco Martín (2024)
Introduction: Pulmonary tuberculosis is a public health problem in several countries in Latin America and the world, due to its high incidence and social impact. The objective of this study was to evaluate the impact of the CCT program on the incidence of pulmonary tuberculosis (PTB) in Health Region III of the Dominican Republic during 2012-2018.  Method: An observational study with a mixed ecological design was carried out. New cases of TBP and social programs were analyzed. The coverage of social programs was the main variable, and the TBP incidence rate was the dependent variable. Other covariates were considered. Results: The results showed that the TBP incidence rate did not decrease in Health Region III despite an increase in the coverage of CCT social programs and a decrease in the poverty level. The CCT "Eating First" program had a significant impact on reducing poverty and other social determinants in Health Region III. Conclusions: Our findings support previous research suggesting that CCT programs are effective in reducing poverty and addressing some social determinants of health. However, they do not support the use of CCTs as an isolated measure to reduce new cases of TBP, since poverty must be addressed in a comprehensive, holistic and inclusive manner to achieve a more significant impact on diseases with high prevalence and endemicity.